KESESUAIAN DAN IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM MENGAKOMODASI PERKEMBANGAN PARA MURID SERTA INTEGRASI NILAI NILAI KARAKTER: DALAM MENGAKOMODASI PERKEMBANGAN PARA MURID SERTA INTEGRASI NILAI NILAI KARAKTER - Lamhatunnisa, Lamhatun; sinta agustin, putri; saputri lubis, salma; Khoir Fadel, Arfakhsyad; munasir, munasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Islamic Religious Education (PAI) curriculum plays a strategic role in shaping students’ faith, morality, and character. To achieve these objectives optimally, the PAI curriculum must be aligned with students’ developmental stages and effectively implemented in educational practice. This article aims to examine the alignment of the PAI curriculum with students’ cognitive, affective, social, and moral-spiritual development, as well as to analyze its implementation in educational settings and the integration of character values. This study employs a library research method by reviewing various sources, including textbooks, scholarly journals, and educational policy documents. The findings indicate that the PAI curriculum has generally been designed in accordance with students’ developmental stages and emphasizes character formation. However, its implementation in practice still faces several challenges, such as gaps in teachers’ competencies, limited facilities, differences in socio-cultural backgrounds, and disparities in digital literacy. Therefore, strengthening teachers’ competencies, promoting instructional innovation, and enhancing collaboration among schools, families, and communities are necessary to ensure that the PAI curriculum functions optimally in shaping a generation that is faithful, morally upright, and socially responsible.